Selective on-surface covalent coupling based on metal-organic coordination template - Shuaipeng Xing (Nature Portfolio, 2019)
Synthesizing precise conjugated nanostructures on a surface requires fine control over the covalent reaction pathways. Here, the authors show that reversible coordinative bonds can be used to template on-surface C-C coupling reactions, guiding the formation of porous organic nanoribbons.